CHANGES OBSERVED IN THE ORAL CAVITY OF PATIENTS WITH OBESITY - Omonova Shodiyona Farkhod kizi (Ustozlar uchun, 2025)
Obesity is a widespread issue around the world and is associated with various chronic diseases, including cardiovascular diseases, diabetes, and even oral cavity disorders. Recent studies have shown that obesity significantly affects oral health. This condition is characterized by a higher prevalence of periodontal diseases, dental caries, halitosis (bad breath), and dry mouth syndrome.